2005
DOI: 10.1002/dvdy.20319
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofcis-element regulating expression of the mouseFgf10 gene during inner ear development

Abstract: Fibroblast growth factor (FGF) signaling is crucial for the induction and growth of the ear, a sensory organ that involves intimate tissue interactions. Here, we report the abnormality of Fgf10 null ear and the identification of a cis-regulatory element directing otic expression of Fgf10. In Fgf10 null inner ears, we found that the initial development of semicircular, vestibular, and cochlear divisions is roughly normal, after which there are abnormalities of semicircular canal/cristae and vestibular developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 65 publications
7
71
0
Order By: Relevance
“…Fgf10 is very strongly expressed in the developing cochlear ganglion and all of the developing inner ear prosensory patches, eventually resolving in the cochlear duct to the broad inner sulcus (Pirvola et al 2000;Pauley et al 2003) immediately medial to the developing inner hair cell, which expresses Fgf8. Fgf10-null mutants have severely deranged vestibular system morphogenesis and abnormalities of cochlear and vestibular innervation (Pauley et al 2003;Ohuchi et al 2005), but cochlear duct defects have not been reported and are currently being assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Fgf10 is very strongly expressed in the developing cochlear ganglion and all of the developing inner ear prosensory patches, eventually resolving in the cochlear duct to the broad inner sulcus (Pirvola et al 2000;Pauley et al 2003) immediately medial to the developing inner hair cell, which expresses Fgf8. Fgf10-null mutants have severely deranged vestibular system morphogenesis and abnormalities of cochlear and vestibular innervation (Pauley et al 2003;Ohuchi et al 2005), but cochlear duct defects have not been reported and are currently being assessed.…”
Section: Discussionmentioning
confidence: 99%
“…(51) Combined with its role in hair follicle stem cells, (20) the early expression and massive reduction of ear development in Gata3 null mice (41) shows that this gene plays an important role in setting up the proliferation capacity of the otocyst through interactions with SMADs (51) and FGFs. (52) Some evidence for PAX signaling affecting SMADS exists for thyroid development, (53) but this has not been demonstrated for the ear. However, an absence of sensory neurons has been claimed for Pax2 null mice, (42) a claim that needs to be reexamined with more sophisticated techniques.…”
Section: Turning Embryonic Ectoderm Cells Into Otic Neurosensory Cellmentioning
confidence: 99%
“…(27,29,30) In addition, FGF's likely signaling through FGFR2B (80) affect morphogenesis and neurosensory formation. (52,63,81,82) How signals generated by these diffusible factors combine with local signals such as EYA1 (48) to maintain and alter bHLH-gene-mediated neuronal progenitor specification and proliferation is unclear. Based on the limited data and expanding general principles validated in other systems, the following tentative conclusions can be drawn: in general, neuronal stem cells express both glial and neuronal markers such as GFAP and Nestin (79) but also the activator and repressor-type bHLH genes.…”
Section: Molecular Basis Of Otic Neuronal Stem Cell Maintenance and Ementioning
confidence: 99%
“…Disruption of FgfR1, the other potential receptor for FGF10, causes defects in the organ of Corti associated with the reduced proliferation of the precursor pool that generates the auditory sensory epithelium (Pirvola et al, 2002). Moreover, FGF10 signalling was proposed to be regulated by GATA3, a zinc finger transcription factor (Ohuchi et al, 2005;Lillevali et al, 2006).…”
Section: Diffusible Factors Involved In Inner Ear Neurogenesismentioning
confidence: 99%
“…Disruption of FgfR1, the other potential receptor for FGF10, causes defects in the organ of Corti associated with the reduced proliferation of the precursor pool that generates the auditory sensory epithelium (Pirvola et al, 2002). Moreover, FGF10 signalling was proposed to be regulated by GATA3, a zinc finger transcription factor (Ohuchi et al, 2005;Lillevali et al, 2006).Finally, mouse FGF15 is the homologue of chicken and human FGF19 (Wright et al, 2004). Mesodermal chicken Fgf19 has been implicated in otic induction (Ladher et al, 2000;Wright et al, 2004) and it is expressed both in the ganglionar neuroblasts delaminating from the otic epithelium and in the CVG ( Figure 1B).…”
mentioning
confidence: 99%